2009
DOI: 10.1016/j.ajhg.2009.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Copy-Number Mutations on Chromosome 17q24.2-q24.3 in Congenital Generalized Hypertrichosis Terminalis with or without Gingival Hyperplasia

Abstract: Congenital generalized hypertrichosis terminalis (CGHT) is a rare condition characterized by universal excessive growth of pigmented terminal hairs and often accompanied with gingival hyperplasia. In the present study, we describe three Han Chinese families with autosomal-dominant CGHT and a sporadic case with extreme CGHT and gingival hyperplasia. We first did a genome-wide linkage scan in a large four-generation family. Our parametric multipoint linkage analysis revealed a genetic locus for CGHT on chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 29 publications
7
93
0
2
Order By: Relevance
“…The Carney Complex is characterized by pigmented lesions of the skin and mucosae, myxomas, endocrine tumors or endocrine overactivity and schwannomas. Sun et al 14 reported three Han Chinese families with congenital generalized hypertrichosis terminalis segregating with a small microdeletion involving chromosome bands 17q24.2-q24.3 for which MAP2K6 (mitogen-activated protein kinase kinase 6) was the best candidate gene. Here we present four previously unreported patients with overlapping microdeletions at chromosome band 17q24.2.…”
Section: Introductionmentioning
confidence: 99%
“…The Carney Complex is characterized by pigmented lesions of the skin and mucosae, myxomas, endocrine tumors or endocrine overactivity and schwannomas. Sun et al 14 reported three Han Chinese families with congenital generalized hypertrichosis terminalis segregating with a small microdeletion involving chromosome bands 17q24.2-q24.3 for which MAP2K6 (mitogen-activated protein kinase kinase 6) was the best candidate gene. Here we present four previously unreported patients with overlapping microdeletions at chromosome band 17q24.2.…”
Section: Introductionmentioning
confidence: 99%
“…The original interest in the 17q24.2-24.3 chromosomal region was in the MAP2K6 gene (Sun et al, 2009). While other MAPK pathway proteins have been implicated in both hair growth and gingival overgrowth conditions, there was some debate about the MAP2K6 gene involvement in the combined phenotype (Hart et al, 2002;Sun et al, 2009).…”
Section: Candidate Gene Microarray and Rt-qpcr Analysis Of The Map2mentioning
confidence: 99%
“…It is associated with chromosomal region 17q24.2-24.3 (Sun et al, 2009). Of interest, this region contains several members of the ATP binding cassette transporter family A (ABCA) family of genes, MAP2K6, and the PITPNC1 gene.…”
Section: Comparison Of Hhg Microarray Gene Lists To Chromosomal Loci mentioning
confidence: 99%
See 2 more Smart Citations